The Critical Shoulder Angle Can be Accurately and Reliably Determined from Three‐Dimensional Computed Tomography Images - Yi Long , MD; Huijun Hu , MD; Chuanhai Zhou , MD; Jingyi Hou , MD; Zhiling Wang , MD; Min Zhou , MD; Dedong Cui , MD; Xiaoding Xu , MD; Rui Yang , MD (Orthopaedic Surgery, 2023)
Objective Anteroposterior (AP) radiographs do not necessarily offer the optimal approach to measuring the critical shoulder angle (CSA) due to the malposition of the scapula. Three‐dimensional computed tomography (3D‐CT) may offer some advantages, including the ability to rotate the scapula for position alignment and pre‐operative planning for reducing CSA. This study aimed to investigate the accuracy and reliability of CSA measurement in 3D‐CT and to determine whether there is an association between CSA and rotator cuff tears (RCTs). Methods In this retrospective study we identified 200 patients who received shoulder arthroscopy from 2019 to 2021, including 142 patients (81 females, 61 males) with RCTs and 58 patients (14 females, 44 males) with non‐RCTs. For each participant, CSA was measured from standard shoulder AP radiographs and anterior views of 3D‐CT of the scapula by two independent assessors. Inter‐ and intra‐observer agreements were assessed by the intraclass correlation coefficient (ICC). The relationship between the two measurement methodologies was determined by Spearman's correlation coefficient and Bland–Altman plots. Discriminative capacity was calculated by using receiver operating curve (ROC) analyses in the whole cohort and age sub‐groups above and below 45 years. Results We found perfect inter‐observer (ICC >0.96) and intra‐observer (ICC >0.97) reliabilities for CSA measurements obtained from the standard AP radiographs and the 3D‐CT. There was a strong correlation between the two methods (r = 0.960, P < 0.001). The mean CSA was 31.7° ± 4.2° in the standard AP radiographs and 31.8° ± 4.4° in the 3D‐CT (mean difference 0.02°, P = 0.940; bias 0.02°, limits of agreement −2.29° to +2.33°). ROC analysis of the whole cohort showed that the CSA measured in the standard AP radiographs (area under the ROC curve [AUC] = 0.812, P < 0.001) and the 3D‐CT (AUC = 0.815, P < 0.001) predicted RCT with high confidence. ROC analysis of patients aged ≥45 years showed that the CSA measured from the standard AP radiographs (AUC = 0.869, P < 0.001) and the 3D‐CT (AUC = 0.870, P < 0.001) were very good at predicting RCTs. Conclusion CSA measured from standard AP radiographs and 3D‐CT showed high consistency, and the CSA could be accurately and reliably measured using 3D‐CT. CSAs measured from standard AP radiographs and 3D‐CT could predict RCTs, especially in patients aged ≥45 years.